Banks, Government Bonds, and Default : What do the Data Say? - Gennaioli, Nicola (IMF Working Papers; Working Paper ;, 2014)
We analyze holdings of public bonds by over 20,000 banks in 191 countries, and the role of these bonds in 20 sovereign defaults over 1998-2012. Banks hold many public bonds (on average 9% of their assets), particularly in less financially-developed countries. During sovereign defaults, banks increase their exposure to public bonds, especially large banks and when expected bond returns are high. At the bank level, bondholdings correlate negatively with subsequent lending during sovereign defaults. This correlation is mostly due to bonds acquired in pre-default years. These findings shed light on alternative theories of the sovereign default-banking crisis nexus.